Three-point Green function of the stress-energy tensor in the AdS/CFT correspondence - FROLOV, SERGEY (Institute of Physics, 1999)
We compute the three-point function of the stress-energy tensor in d-dimensional conformal field theory CFT from AdSd11 gravity. For d54 the coefficients of the three linearly independent conformally covariant forms entering the three-point function are exactly the same as given by the free-field computations in the N54 SYM theory just as expected from the known renormalization theorems. For d53 and d56 our results give the value of the corresponding three-point function in the theories of strongly coupled N58 superconformal scalar and ~2,0! tensor multiplets, respectively
PUBLISHED
Keywords: Mathematics; Particle physics and field theory; Gravity; tensor multiplets